2021
DOI: 10.1016/j.omtn.2021.08.015
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 correction of OPA1 c.1334G>A: p.R445H restores mitochondrial homeostasis in dominant optic atrophy patient-derived iPSCs

Abstract: Autosomal dominant optic atrophy (DOA) is the most common inherited optic neuropathy in the United Kingdom. DOA has an insidious onset in early childhood, typically presenting with bilateral, central visual loss caused by the preferential loss of retinal ganglion cells. 60%–70% of genetically confirmed DOA cases are associated with variants in OPA1 , a ubiquitously expressed GTPase that regulates mitochondrial homeostasis through coordination of inner membrane fusion, maintenance of cris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…As we wanted to achieve a permanent correction of the GPR143 intron 7 mutation, we explored the more recent option of genome editing by using the CRISPR-Cas system to promote HDR, a strategy that has previously been proven feasible by other groups. 41 , 44 , 55 For its delivery, we opted for an RNP formulation instead of a plasmid-based approach. RNPs are less toxic, ready to act, and not constantly produced in the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…As we wanted to achieve a permanent correction of the GPR143 intron 7 mutation, we explored the more recent option of genome editing by using the CRISPR-Cas system to promote HDR, a strategy that has previously been proven feasible by other groups. 41 , 44 , 55 For its delivery, we opted for an RNP formulation instead of a plasmid-based approach. RNPs are less toxic, ready to act, and not constantly produced in the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we briefly highlight some of the iPSC-derived RGC disease models that have been developed using 2D and 3D culture approaches. Several teams have now made patient derived and CRISPR/Cas edited iPSC lines for the investigation of glaucoma [ 199 , 209 , 210 ], LHON [ 211 , 212 , 213 , 214 ], and DOA [ 215 , 216 , 217 , 218 ].…”
Section: Experimental Models Of Retinal Ganglion Cell Degeneration To Study Oxidative Stressmentioning
confidence: 99%
“…Several teams have also begun trying to model DOA from patients with mutations in the OPA1 gene [ 215 , 216 , 217 , 218 ]. Chen et al found that OPA1 mutation increased necrosis and apoptosis in the patient iPSCs and could not efficiently differentiate them into RGCs using their initial methodology.…”
Section: Experimental Models Of Retinal Ganglion Cell Degeneration To Study Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…As the mutations are all engineered into the same isogenic cell line background, the effects observed are due to the individual mutations and not confounded by factors such as genetic background and sex ( Anastasaki et al., 2020 ). As an alternative approach, patient hiPSC lines can be compared with gene-corrected isogenic control cell lines ( Figure 2 ) ( Sladen et al., 2021 ).
Figure 2 Generation of isogenic pairs of cell lines that differ by a single genetic modification Isogenic control cell lines can be created from healthy pluripotent stem cells to model the effect of a specific patient population.
…”
Section: Introductionmentioning
confidence: 99%